Susana Gaspar, Cátia Moreso, Fernando Guimarães, Nuno Vieira de Almeida, Fernando Lopes-Graça: Songs and Folk Songs (CD Naxos, 2018) - Marinho, Helena (Revista Portuguesa de Musicologia, 2019)
Recensão: Susana Gaspar, Cátia Moreso, Fernando Guimarães, Nuno Vieira de Almeida, Fernando Lopes-Graça: Songs and Folk Songs